Hoe, harrow, hoe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Simple straightforward technologies and tools still provide the basis for much agricultural production and processing. After decades of dissemination strategies, experimental workshops and small-scale industrialisation, a spade is a spade is a...